Comparative study of honeys and herbhoneys quality paramertes - Novák, Anna; Kovács, Béla; Czipa, Nikolett (Acta Agraria Debreceniensis, 2017)
Honey is one of the oldest known and consumed food. Besides the pleasant sweet taste it has been consumed because of the favorable health benefits. In addition to large number of honey plants there are many popular herbals which cannot serve as a nectar source. The herbhoney has been developed that consumers can joy the pleasant properties of herbals and honeys positive impact on the same product. In our research we compare the quality parameters of honeys and herbhoneys to each other and with the relevant regulation.